2017
DOI: 10.1038/ncomms15758
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide and derivatives block ethylene biosynthesis by inhibiting ACC oxidase

Abstract: Ethylene is an important phytohormone that promotes the ripening of fruits and senescence of flowers thereby reducing their shelf lives. Specific ethylene biosynthesis inhibitors would help to decrease postharvest loss. Here, we identify pyrazinamide (PZA), a clinical drug used to treat tuberculosis, as an inhibitor of ethylene biosynthesis in Arabidopsis thaliana, using a chemical genetics approach. PZA is converted to pyrazinecarboxylic acid (POA) in plant cells, suppressing the activity of 1-aminocyclopropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 73 publications
3
55
0
Order By: Relevance
“…The longer vase life of the flowers treated with 2,4-PDCA may be caused by the pronounced inhibition of ethylene production as compared with the acceleration of flower opening. Recently, Sun et al (2017) reported that 2-PCA blocks ethylene biosynthesis by inhibiting the ACC oxidase action, but 3-PCA does not. Therefore, 3-PCA, and probably 3-PCA amide, promoted only flower opening, but did not inhibit ethylene production, resulting in a shorter vase life than that of 2,4-PDCA-treated flowers.…”
Section: Resultsmentioning
confidence: 99%
“…The longer vase life of the flowers treated with 2,4-PDCA may be caused by the pronounced inhibition of ethylene production as compared with the acceleration of flower opening. Recently, Sun et al (2017) reported that 2-PCA blocks ethylene biosynthesis by inhibiting the ACC oxidase action, but 3-PCA does not. Therefore, 3-PCA, and probably 3-PCA amide, promoted only flower opening, but did not inhibit ethylene production, resulting in a shorter vase life than that of 2,4-PDCA-treated flowers.…”
Section: Resultsmentioning
confidence: 99%
“…S13). However, additional data are needed to exclude the inhibition of enzymes in auxin biosynthesis pathway directly by AVG (Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…a,b), suggesting that basal levels of endogenous ethylene are required to maintain normal root elongation. To further examine whether the short root phenotype of the osdof15 mutants was due to the overproduction of ethylene, we used the ethylene biosynthesis inhibitor POA (Sun et al ., ). Application of 50 μM POA largely rescued the short root phenotype of osdof15 (Figs c,d, S5a,b).…”
Section: Resultsmentioning
confidence: 97%